2022
DOI: 10.1016/j.jid.2021.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Immunophenotypic Analysis Reveals Differences in Circulating Immune Cells in the Peripheral Blood of Patients with Segmental and Nonsegmental Vitiligo

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 38 publications
0
12
0
1
Order By: Relevance
“…Additionally, there is evidence on a number of melanocyte-specific antibodies found in the sera of vitiligo patients which correlate with the disease’s activity. The presence of anti-melanocyte antibodies indicates a systemic immune activation in non-segmental vitiligo [ 14 , 153 ]. Furthermore, recent study revealed increased proportion of circulating memory B cells and decreased levels of naive B cells in active vitiligo, which is followed by an increase in circulating T follicular helper (cTfh) cells [ 154 ].…”
Section: Current Concepts In Immunopathogenesis Of Vitiligomentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, there is evidence on a number of melanocyte-specific antibodies found in the sera of vitiligo patients which correlate with the disease’s activity. The presence of anti-melanocyte antibodies indicates a systemic immune activation in non-segmental vitiligo [ 14 , 153 ]. Furthermore, recent study revealed increased proportion of circulating memory B cells and decreased levels of naive B cells in active vitiligo, which is followed by an increase in circulating T follicular helper (cTfh) cells [ 154 ].…”
Section: Current Concepts In Immunopathogenesis Of Vitiligomentioning
confidence: 99%
“…In NSV, immune activation is systemic, whereas in SV, a local cytotoxic reaction is involved. Furthermore, unlike in SV, NSV patients have fewer regulatory T cells, making them more susceptible to other systemic autoimmune diseases [ 14 ]. The following manuscript will focus on NSV, further referred to as vitiligo.…”
Section: Introductionmentioning
confidence: 99%
“…In nonsegmental vitiligo, systemic immune activation occurs, whereas in the segmental type, there is only a localized cytotoxic reaction, probably due to melanocyte mosaicism. 93 Tregs are unaffected in the peripheral blood of segmental vitiligo when compared to controls. On the other hand, Tregs are reduced in nonsegmental vitiligo and associated with other autoimmune comorbidities, less frequent in segmental vitiligo.…”
Section: Immunological Changesmentioning
confidence: 90%
“…These data show that in contrast to patients with NSV, no increased systemic immunity is found in patients with SV, indicating that SV pathogenesis is associated with a localized cytotoxic reaction targeting epidermal melanocytes. 52…”
Section: Biochemical Ultrastructural Immunological and Serological Co...mentioning
confidence: 99%